La data di Leonzio presbitero di Costantinopoli - Voicu, Sever J. (Augustinianum, 2016)
According to Cornelis Datema, the still mysterious Leontius of Con-stantinople preached sometime around 557, whereas Michel Asmus places him between the end of the 4th century and the mid-5th century. This paper contends that the memory of a deceased bishop that closes the homily Nat. refers to Theodore I, patriarch of Constantinople, who died on 28 December 687. The article also shows that Leontius cannot possibly have lived earlier than the mid-6th century.